Financial Health Indicators and Organizational Transformation Strategies: A Comprehensive Multi-Model Analysis Through Systematic Literature Review of PT NPLC's Performance Evolution 2015-2024 - Ayu Prabandari; Ana Noveria (Green Publisher Indonesia, 2026)
The era of digital transformation has resulted in a fundamental paradigm shift in organizational management, where financial health indicators have become the main determinants of the success of organizational transformation strategies. This study aims to comprehensively analyze the evolution of PT NPLC’s performance through a systematic literature review that integrates financial health indicators and organizational transformation strategies for the 2015–2024 period. The research method employs a systematic literature review following the PRISMA 2020 protocol, using a multi-model analysis that integrates 22 quantitative metrics and qualitative frameworks (SWOT, PESTEL, Porter’s Five Forces). The results show that the implementation of the organizational transformation strategy in 2021 had a significant positive impact, with an increase in Net Profit Margin from 4.98% to 13.83% (p = 0.0014), a strengthening of the Current Ratio from 1.05 to 1.42 (p = 0.0136), and a decrease in the Debt Ratio from 0.62 to 0.41 (p = 0.0143). The study concludes that an integrated digital transformation approach can create long-term value despite trade-offs in asset productivity. Therefore, organizations need to develop a multi-model analysis framework to optimize transformation strategies based on financial health indicators.